Stories for Hope–Rwanda: a psychological–archival collaboration to promote healing and cultural continuity through intergenerational dialogue - Wallace, David A.; Pasick, Patricia; Berman, Zoe; Weber, Ella (Archival Science, 2014)
Can archives help heal and extend the benefit of therapeutic interventions in a post-genocide environment? We sought to probe this question through an uncommon collaborative documentation and research project linking psychology and archival science: Stories for Hope–Rwanda (SFH). This intergenerational dialogue project between youth and elder pairs in post-genocide Rwanda draws upon a collective narrative model from psychology and both community and participatory models from archives. The paper reports on three aspects of this endeavor: (1) description of SFH as a process of dialogue generation and archiving; (2) content analysis of the knowledge post-genocide youth sought from their elders; and (3) a qualitative evaluation of what benefits youth and elder pairs reported 6–12 months after their dialogue session, including how participants made use of a personal copy of their dialogue and their decision making and perceptions on making their dialogues more widely available. Specifically, we wanted to know whether psychological benefits would accrue if the silences about genocide could be breached by intergenerational dialogues and whether audio recordings of the dialogues archived for personal, national, and international use could motivate youths and elders over the hurdle of silence and extend the benefits of the dialogues to others. In contrast to interview-driven genocide testimonies, each youth asked an elder to answer some burning questions about the past. In response, elders were directed to share personal, true, and positively helpful stories from their past experiences. Through these efforts, SFH consciously sought to democratize the creation, control, custody, and access to the archive resulting from the recorded dialogues. Based on our analysis, we found that youth were eager to learn most about the genocide (causes, prevention, and stories of loss and survival), followed by family history, marriage, Rwandan culture, living as an orphan, and strategies for forgiveness and reconciliation. We also found that the archival component of the project significantly contributed to both the motivation for participation and the extent of participants’ healing. We conclude that this approach can be productively expanded to other post-conflict and post-genocide communities where silence about a traumatic past reigns triumphant and undermines the ability of youth to map a positive future.
Other Publications
Keywords: A&DwP website; Community archiving; Genocide; Participatory archiving; Psychology; Rwanda; Trauma